2014
DOI: 10.1016/j.jobcr.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cysts and tumors around the retained and unerupted third molars in the Indian population

Abstract: The results indicate that cysts and tumors do develop in a relatively small but still considerable minority of patients. The fact that a considerable number of patients had no signs or symptoms indicating pathology is certainly worth considering. Consultation should be sought from dental specialists if there are symptoms in the third molar region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
1
22
0
5
Order By: Relevance
“…In presence of pathological changes associated with impaction like cysts, tumours, destruction of adjacent teeth, non-restorable carious lesion, there is no disagreement for tooth extraction. [11,12] The incidence of cysts and tumours present around the impacted third molar varies greatly in various studies but in our study, dentigerous cyst have the highest incidence (22.35%) followed by ameloblastoma (14.11%), odontogenic keratocyst (9.4%) and calcifying cystic odontogenic tumour (2.35%).…”
Section: Discussionmentioning
confidence: 61%
“…In presence of pathological changes associated with impaction like cysts, tumours, destruction of adjacent teeth, non-restorable carious lesion, there is no disagreement for tooth extraction. [11,12] The incidence of cysts and tumours present around the impacted third molar varies greatly in various studies but in our study, dentigerous cyst have the highest incidence (22.35%) followed by ameloblastoma (14.11%), odontogenic keratocyst (9.4%) and calcifying cystic odontogenic tumour (2.35%).…”
Section: Discussionmentioning
confidence: 61%
“…The incidence of pathology associated with asymptomatic impacted third molars in the Indian population has been documented by Patil et al 49 and Vigneswaran et al 50 Both studies agree that the incidence of cysts or tumors in the third molars is very low. Patil et al 49 reported that a considerable number of patients had disease-free third molars. However a minority yet a significant number of the patients were identified with pathology.…”
Section: Indian Population Studiesmentioning
confidence: 86%
“…Specific type of impacted third molar causing distal caries in second molar was identified and recorded. Impacted mandibular third molar were classified as per the standard Pell & Gregory classification as vertical, mesioangular, distoangular, horizontal and others [7][8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%